2018
DOI: 10.1002/lary.27114
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin does not prevent growth of vestibular schwannomas: A case‐control study

Abstract: 3b. Laryngoscope, 128:2139-2144, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…The correlation between the PET assessment and inflammatory cell density was preserved and so this did not detract from the potential of 11 C-( R )-PK11195 as a biomarker, but the reason for high immunohistochemical TSPO labeling in this case could not be clarified. Previous studies have shown that tumor size itself is a predictive marker of VS growth, 49 although this is not universally accepted. Separating the relative contributions of tumor size and growth rate to 11 C-( R )-PK11195 specific binding from our data is difficult as the growing tumors were also statistically significantly larger.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the PET assessment and inflammatory cell density was preserved and so this did not detract from the potential of 11 C-( R )-PK11195 as a biomarker, but the reason for high immunohistochemical TSPO labeling in this case could not be clarified. Previous studies have shown that tumor size itself is a predictive marker of VS growth, 49 although this is not universally accepted. Separating the relative contributions of tumor size and growth rate to 11 C-( R )-PK11195 specific binding from our data is difficult as the growing tumors were also statistically significantly larger.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary Hunter et al showed no effect of ASA intake on tumor growth in a series of 564 VS [13]. A most recent study assessed 437 cases and found no impact on ASA as well [21]. The Congress of Neurological Surgeons recently recommended the administration of aspirin for patients with vestibular schwannomas as an antiproliferative treatment [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort there was no association between tumor extension and MIB1 expression. Suggestions have been made that the current tumor size is a factor influencing future tumor growth [21]. However, in the study by MacKeith and colleagues, growth was defined as 2 mm increase in diameter, which does not represent the true percentual increase of the tumor volume and is obsolete for tumor volume and growth assessment [21, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a significant inverse association with aspirin users and tumour growth (OR 0.32, 95% CI 0.11-0.91) [82]. Although two similar retrospective analyses did not find an inverse association, they did not observe increased tumour growth with aspirin or other NSAID users [83,84]. Therefore, a level 3 recommendation exists in the CNS stating aspirin may be considered for patients undergoing observation [73].…”
Section: Emerging Treatmentsmentioning
confidence: 96%